Bayes Estimator of the Parameter and Reliability Function of Marshall-Olkin Extended Exponential Distribution Using Hybrid Type-II Censored Data. Issue 3 (3rd May 2016) - Yadav, Abhimanyu Singh; Singh, Sanjay Kumar; Singh, Umesh
Abstract: In this article, we considered the problem of estimation for the parameters and reliability characteristics of Marshall-Olkin Extended exponential distribution (MOEED) using hybrid Type-II censored data. For estimation, the maximum likelihood estimators (MLE's) andBayes estimators are constructed. In Bayesian paradigm, Markov Chain Monte Carlo method has been used to compute the Bayes estimates. The 95% asymptotic confidence intervals and highest posterior density intervals for the parameters are also obtained. A comparative study between maximum likelihood estimators and Bayes estimators has been performed using simulation technique. Lastly, a real data set is also analysed for illustration.